Squaraine Dye Square-460 as a Marker of Membrane Cryodamage - Goryachaya, Irina P.; Dyubko, Tatyana S.; Zinchenko, Vasiliy D.; Buryak, Irina A.; Patsenker, Leonid D.; Tatarets, Anatoliy L. (Problems of Cryobiology and Cryomedicine, 2013)
N/A Probl Cryobiol Cryomed 2013; 23(4):347–350.